The Influence of Nutrition Competency Test Assistance Activities on Students - Riska Rusydi; Rina Hasniyati (Lembaga Pengembangan Kinerja Dosen, 2025)
The competence of health workers is obtained from passing the competency test taken by each health student. The failure to achieve the target for passing the competency test needs to be given more attention because it is related to the quality of graduates of a university. One of the ways to increase graduation is by providing assistance with special knowledge related to competency tests. This study aims to see the effect of providing nutrition competency test mentoring to nutrition students on competency test knowledge. This is an experimental study with a pre-experimental design (one group pretest-posttest) which was carried out by providing competency test assistance 3 times to respondents which was carried out in August 2024. Data processing was carried out using a paired sample t-test statistical test. There is an effect of providing competency test assistance on knowledge of the Nutrition competency test in D-III Nutrition students at the Ministry of Health, Padang Health Polytechnic (P = 0.000).